Metode Iterasi Tiga Langkah dengan Orde Konvergensi Tujuh - Wartono Wartono; Mayumi Istiqomah (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
Potra-Ptak method and Newton’s variant are one of iteration method which it uses for determineroot of nonlinear similarity with third order convergence. In this Final Task, the writer has done modifiedcomposite of Potra-Ptak method and Newton’s variant by enganging θ1 and θ2 parameter and adding thethird step which approximation fꞌ(zn) using second order Lagrange interpolation. Based on the researchresult new iteration method have seventh order convergence with θ1=3 and θ2=−2. Each of iteration needsfour f evaluation function which they are f(xn), fꞌ(xn), f(yn) and f(zn) with efficiency index of 71/4≈1,6265.Numerical simulation is given to show the performance of composite Potra-Ptak method and Newton’svariant.Keywords: composite of potra-ptak method and newton’s variant, efficiency index, Lagrange interpolation,nonlinear equation, order convergence